2017
DOI: 10.1016/j.infbeh.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Is level of prematurity a risk/plasticity factor at three years of age?

Abstract: Children born preterm have poorer outcomes than children born full-term, but the caregiving environment can ameliorate some of these differences. Recent research has proposed that preterm birth may be a plasticity factor, leading to better outcomes for preterm than full-term infants in higher quality environments. This analysis uses data from two waves of an Irish study of children (at 9 months and 3 years of age, n=11,134 children) and their caregivers (n=11,132 mothers, n=9,998 fathers) to investigate differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 68 publications
2
35
2
Order By: Relevance
“…135 Two studies have directly tested diathesis stress compared to differential susceptibility models to determine a framework that characterizes how prematurity interacts with environmental susceptibility. 29,136 In this line of research, Hadfield et al 136 found effect of maternal factors, including attachment and maternal distress, were similar between full-term and PT children; however, paternal distress effect on child cognitive and social development were moderated by prematurity. Since adversity of parental distress (but not the presence of positive emotional factors) drove the interaction between birth status and outcome, Hadfield et al 136 tentatively interpret paternal distress effects within a diathesis stress framework.…”
Section: Clinical Pathologymentioning
confidence: 97%
See 1 more Smart Citation
“…135 Two studies have directly tested diathesis stress compared to differential susceptibility models to determine a framework that characterizes how prematurity interacts with environmental susceptibility. 29,136 In this line of research, Hadfield et al 136 found effect of maternal factors, including attachment and maternal distress, were similar between full-term and PT children; however, paternal distress effect on child cognitive and social development were moderated by prematurity. Since adversity of parental distress (but not the presence of positive emotional factors) drove the interaction between birth status and outcome, Hadfield et al 136 tentatively interpret paternal distress effects within a diathesis stress framework.…”
Section: Clinical Pathologymentioning
confidence: 97%
“…29,136 In this line of research, Hadfield et al 136 found effect of maternal factors, including attachment and maternal distress, were similar between full-term and PT children; however, paternal distress effect on child cognitive and social development were moderated by prematurity. Since adversity of parental distress (but not the presence of positive emotional factors) drove the interaction between birth status and outcome, Hadfield et al 136 tentatively interpret paternal distress effects within a diathesis stress framework. Gueron-Sela et al 29 also compared effects of caregiving environment on PT child outcomes relative to a full-term comparison group with results more consistent with a differential susceptibility hypothesis.…”
Section: Clinical Pathologymentioning
confidence: 97%
“…VLBW and preterm had a higher incidence of the abnormal neurobehavioral score (46%) than Full-term at1 month and 3 months (40%). Very preterm and late preterm both are known independent significant risk factors for poor outcomes at 3 months age and have poor neurodevelopment outcomes than full-term infants [11].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors also have an impact on premature children's psychological development and behavior in negative, as well as in positive ways (Erica et al, 2015). According to the "diathesis stress" model, premature children are more susceptible to the negative influence of the environment (Hadfield, Fearghal, & Gerow, 2017). The interaction of a child with a significant adult is the most important environmental factor during the first year of his life.…”
Section: Discussionmentioning
confidence: 99%
“…Such separation may negatively affect the psychological state of a parent: it is common for parents to experience fear of their child's potential death. It has been identified that this kind of parental anxiety further affects the neurocognitive and socioemotional development of a premature child (Hadfield et al, 2017). While parenting at home, any negative emotions experienced by the parents may be further aggravated by their realization that the child requires special care and protection, which in turn may cause parents to feel inadequate and result in a disadaptive attachment between the parents and the child.…”
Section: Introductionmentioning
confidence: 99%